Impact of corticosteroids on the efficacy of CD19/22 CAR-T cell therapy in pediatric patients with B-ALL: a single-center study - Yang, Jing; Zhang, Jing; Wan, Xinyu; Cai, Jiaoyang; Wang, Tianyi; Yang, Xiaomin; Li, Wenjie; Ding, Lixia; Song, Lili; Miao, Yan; Wang, Xiang; Ma, Yani; et al. (Frontiers in Pediatrics, 2025)
Corticosteroids are used for toxicity management-raising concerns about whether they may affect Chimeric antigen receptor T-cell (CAR-T) anti-leukemic effects. Here we retrospectively analyzed relapsed or refractory B-ALL patients (<20 years old) treated with our center preparative CD19/22 CAR T cells (Trial Registration No. ChiCTR2000032211). Among 194 patients evaluated, 88% had any grade CRS reaction. We defined two sub-groups based on disease burden. In which 75 cases in the low-disease burden(LDB) group (MRD<5%, no extramedullary disease), there was no significant difference between the use of steroids and the EFS (p = 0.21) and OS (p = 0.26), and the same with 119 cases in the high-disease burden(HDB) group. When eliminate the effect of consolidative transplantation on prognosis, the EFS of patients who did not use steroids was better (p = 0.037) in the LDB group, but the difference is not significant in the HDB group. The median cumulative dexamethasone-equivalent dose was 0.56 mg/kg, and the EFS and OS were similar among different cumulative dose groups. Also, there was no difference in the recovery of B cells and the expansion of the CAR T-cell copies. In conclusion, under the guidance of current CRS prevention and control measures, rational use of corticosteroids does not affect the clinical efficacy and overall survival of CAR-T therapy in B-ALL patients, and also does not affect the persistence of CAR T cells in vivo, but the dosage threshold needs further clinical or experimental verification.